GAMBLING ENTERTAINMENT IN THE HOSPITALITY INDUSTRY - Шидловська, Олена; Арпуль, Оксана (SWorldJournal, 2024)
The article is dedicated to analyzing hotels with gambling facilities in Ukraine and their impact on the country's tourism development. After the adoption of the law on state regulation of the gambling business, hotels were granted the opportunity to orga